Long-range organization of intestinal 2D-crypts using exogenous Wnt3a micropatterning - Enara Larrañaga; Miquel Marin-Riera; Aina Abad-Lázaro; David Bartolomé-Català; Aitor Otero; Vanesa Fernández-Majada; Eduard Batlle; James Sharpe; Samuel Ojosnegros; Jordi Comelles; Elena Martinez (Nature Communications)
Abstract Intestinal epithelial cells are segregated into proliferative crypts and differentiated regions. This organization relies on specific signals, including Wnt3a, which regulates cell proliferation within crypts, and Eph/Ephrin, which dictates cell positioning along the crypt-villus axis. However, studying how the spatial distributions of these signals influences crypt-villus organization is challenging both in vitro and in vivo. Here we show that micropatterns of Wnt3a can govern the size, shape and long-range organization of crypts in vitro. By adjusting the spacing between Wnt3a ligand patterns at the microscale over large surfaces, we override endogenous Wnt3a to precisely control the distribution and long-range order of crypt-like regions in primary epithelial monolayers. Additionally, an agent-based model integrating Wnt3a/BMP feedback and Eph/Ephrin repulsion effectively replicates experimental tissue compartmentalization, crypt size, shape, and organization. This combined experimental and computational approach offers a framework to study how signaling pathways help organize intestinal epithelial tissue.